Induction of EAE by T cells specific for alpha B-crystallin depends on prior viral infection in the CNS - Verbeek, Richard; van Dongen, Henrike; Wawrousek, Eric F.; Amor, Sandra; van Noort, Johannes M. (International immunology, 2007)
While myelin-reactive T cells are widely believed to play a pathogenic role in multiple sclerosis (MS), no substantial differences appear to exist in T-cell responses to myelin antigens between MS patients and healthy subjects. As an example, indistinguishable peripheral T-cell responses and serum antibody levels have been found in MS patients and healthy controls to alpha B-crystallin, a dominant antigen in MS-affected brain myelin. This suggests that additional factors are relevant in allowing myelin-reactive T cells to become pathogenic. In this study, we examined whether the inflammatory state of the CNS is relevant to the pathogenicity of alpha B-crystallin-specific T cells in mice. In normal mice, T-cell responses against alpha B-crystallin are limited by robust immunological tolerance. Reactive T cells were therefore generated in alpha B-crystallin-deficient mice, and these T cells were transferred into C57BL/6 recipients. While such a transfer in itself never induced any clinical signs of experimental autoimmune encephalomyelitis (EAE) in healthy recipient mice, acute EAE could be induced in animals that had been infected 7 days before with the avirulent A7(74) strain of Semliki Forest virus (SFV). SFV infection alone did not induce clinical disease, nor did it alter the expression levels of the target antigen. Our findings indicate that at least in mice, alpha B-crystallin-specific T cells can trigger EAE but only when prior viral infection has induced an inflammatory state in the CNS that helps recruit and activate T cells.